Pelatihan peningkatan Softskill dalam pembuatan Curriculum vitae dan Portofolio di SMA Katolik Santa Agnes Surabaya - Sriwahyuni, Endang; Sri Deviyanti, I Gusti Ayu; Revalino, Diova (Institut Teknologi Adhi Tama Surabaya, 2024)
This community service activity aims to enhance the skills of 12th-grade students at SMA Katolik Santa Agnes Surabaya in creating professional Curriculum Vitae (CV) and portfolios that meet the needs of the job industry and organizations. The training was conducted in response to the lack of understanding and skills among students in preparing documents that are both attractive and relevant for job applications and organizational purposes. The implementation of this activity involved an initial survey, material preparation, direct training, and student mentoring. During the training, students were introduced to techniques for creating CVs and portfolios, from determining the format to utilizing digital applications such as Canva and Microsoft Word. Additionally, students were provided with guidance on how to structure their CVs, include relevant information, and highlight skills and experiences. Mentoring sessions were also provided to assist students facing difficulties in using the applications or compiling their portfolios. The results of this activity showed an improvement in students' skills in preparing more professional CVs and portfolios. Students became more confident in preparing themselves for the job market with documents that meet industry standards. This training is expected to provide long-term benefits for students in various academic and professional contexts.Keywords: Curriculum Vitae, Portfolio, Training, Soft Skills, Digital Applications